Penguatan edukasi praeventif untuk mencegah relaps tb paru di wilayah kerja puskesmas sidomulyo tuah madani pekanbaru - Chairil; Tri Siwi KN; Maswarni; Shinta Dewi Kasih Bratha; Dyah Wulan Ramadhani (Jurnal Pengabdian UntukMu NegeRI, 2025)
Pulmonary Tuberculosis (TB) is a contagious disease that remains a major public health concern due to its easy transmission and high risk of relapse, especially when patients do not complete their treatment. Factors such as low income, irregular medication adherence, and lack of understanding and support from family members are the main causes of relapse. According to data from Sidomulyo Tuah Madani Public Health Center in Pekanbaru City, cases of pulmonary TB are still being found, highlighting the need for continuous preventive (praevenire) education.This community service program aimed to improve the understanding of pulmonary TB patients and their families regarding relapse prevention through an educational approach. The 8-day activity, conducted between April and June, involved 10 patients divided into two groups (5 at 8:00 AM and 5 at 10:00 AM), with a total of 82 participants taking part in counseling and group discussions. Educational topics included the importance of medication adherence, therapy completion, quality of life improvement, and family involvement.The results showed an increase in participants' knowledge and awareness about the importance of completing TB treatment. Although family involvement varied, participants’ enthusiasm indicated that the educational activities were effective in increasing understanding of TB relapse prevention.